Rambut Beruban Prematur pada Anak Usia Tujuh Tahun - Wijaya, Edward; Winaya, Ketut Kwartantaya; Sadeli, Marrietta Sugiarti (Fakultas Kedokteran Universitas Trisakti, 2024)
Premature graying of hair is defined as the occurrence of gray hair, depending on ethnicity, before the age of 30 in Africans, 25 in Asians, and 20 in Caucasians. Premature graying is an important cause of low self-esteem, which often interferes with sociocultural adjustment. Premature graying, known as premature canitis, the exact etiopathogenesis is still unknown, although it has been associated with disorders of premature aging, atopy, and autoimmune diseases. Many pathological conditions have been discussed in relation to premature canitis such as certain medications, deficiencies of Vitamin B12, vitiligo, hypothyroidism, and progeroid syndromes. Premature canitis may occur as an autosomal dominant condition only or associated with premature aging syndromes or various autoimmune. This condition needs to be differentiated from the various genetic hypomelanosis hair disorders. Patients with PGH should be evaluated for metabolic diseases and syndromes. Among the various pharmacotherapeutic management options, calcium pantothenate, PABA, and a combination of calcium pantothenate + PABA can be given. Some herbal agents such as Anu-tailam has been evaluated in a clinical research setting. Hair dye remains the primary treatment modality for cosmetic problems after nutritional supplementation. Lastly, addressing underlying pathological conditions often results in a reversal of the condition in many cases.